Death comes in through the kitchen [large type] - Dovalpage, Teresa, 1966- (A Cuban mystery, 2018)
A San Diego journalist, Matt arrives in Havana to marry his girlfriend, a 24-year-old Cuban woman whom he met through her food blog. When she isn't there to meet him at the airport, he hitches a ride to her apartment and finds her dead in the bathtub. Now the main suspect, Matt embarks on his own investigation to clear his name.